Gene panel for the diagnosis of epidermolysis bullosa: proposal for a viable and efficient approach()() - Mariath, Luiza Monteavaro (An Bras Dermatol, 2021)
BACKGROUND: Epidermolysis bullosa is characterized by cutaneous fragility and blistering. Historically, diagnosis is achieved by immunofluorescence mapping or transmission electron microscopy, both involving biopsy procedures. Genetic analysis, especially through next-generation sequencing, is an important tool for the diagnosis of this disease. In Brazil, access to diagnostic methods is limited, and consequently, most patients do not have an accurate diagnosis. Diagnosis allows the indication of prognosis and genetic counselling of the patient. OBJECTIVES: To evaluate the cost-effectiveness of a gene panel compared to immunofluorescence mapping and transmission electron microscopy by analyzing its benefits, limitations, and economic aspects. METHODS: The gene panel included the 11 main genes associated with epidermolysis bullosa. The techniques were compared, assessing the average cost, advantages, and limitations, through a price survey and literature review. RESULTS: Both immunofluorescence mapping and transmission electron microscopy require skin biopsy, are dependent on the investigator’s expertise, and are subject to frequent inconclusive results. The gene panel is effective for the conclusive diagnosis of epidermolysis bullosa, presents high efficiency and accuracy, is economically feasible, and excludes the need for biopsy. The gene panel allows for prognosis, prenatal genetic diagnosis, and genetic counseling. STUDY LIMITATIONS: It was not possible to find laboratories that perform transmission electron microscopy for epidermolysis bullosa diagnosis in Brazil. CONCLUSION: This study supports the gene panel as the first-choice method for epidermolysis bullosa diagnosis.